ICT and Learning of Mathematics in Nigeria - Umar Abdullahi; Musa Sirajo (MASI Mandiri Edukasi, 2022)
This study empirically reviews ICT and mathematics learning in Nigeria through a systematic literature review. Relevant articles and journals were identified to examine international students' teaching and learning experiences. Research shows that even if teachers believe that students need to understand mathematics or that the use of ICT improves students' development, students still need to solve problems. It may indicate that They do not incorporate her ICT into math classes or use it in traditional ways to impart knowledge. Her effective use of ICT in mathematics education may lead to more learner-centered classroom practices. These changes are widely believed to impact mathematics teaching and to learn positively. For example, ICT can enrich students' mathematics learning experience, increase their interest in mathematics, and change their attitudes toward mathematics. With the proliferation of online e-teaching, flipped classrooms are becoming a new trend in digital learning. The study recommends that ICT tools be made available by all parties to teachers and students with appropriate Internet access to achieve solid academic performance in mathematics. Governments at all levels need to increase their budgets for education and ensure that the money allocated for education is entirely spent.